Optimizing Call Center Productivity through Key Work Environment Factors - Soyangco, Philippe R.; Riva, Ma. Reinadel D.; Narsico, Peter G.; Niere, Marvin Ian E.; Narsico, Lalaine O. (Future Science / FSH-PH Publications, 2024)
This study aims to enhance productivity by fostering a business environment where workers can thrive, similar to a well-functioning ecosystem. It investigates whether factors such as workers' aptitude, training, tools and technology, workload, workplace relationships, working conditions, employee well-being, and satisfaction with compensation positively impact productivity. The study focused on call center agents in Cebu Province, Philippines, with an estimated population of 200,000. Using a Cochran calculation, a sample size of 384 respondents was determined, accounting for a 5% margin of error and a 95% confidence level. Due to challenges in reaching participants, convenience sampling was employed, yielding 385 completed surveys, exceeding the minimum required. Data was collected through a descriptive survey with simple, close-ended questions, validated by call center agents and demonstrating high reliability (Cronbach’s alpha of 0.967). The weighted mean for each predictor and the dependent variable was calculated, and linear regression analyses examined the relationships between predictors and productivity. Additionally, ANOVA within the context of linear regression assessed the significance of these relationships. The findings revealed that the eight identified predictor variables collectively received an average score of 3.277 out of 4.0 from call center agents. All eight predictors—employee aptitude, work training, tools and technology, workload, satisfaction with compensation, employee well-being, working conditions, and workplace relationships—were significant indicators of productivity and explained a portion of the variance in the dependent variable. These results emphasize the need to enhance activities and policies related to all predictor variables, as each significantly impacts productivity. Notably, working conditions and job training received the highest ratings, indicating strong employee satisfaction in these areas. However, urgent attention is needed in addressing employee well-being and satisfaction with compensation, which received the lowest ratings.